Analysis of Students' Understanding of Mathematical Concepts Based on the Discovery Learning Learning Model in Algebraic Form Material - Heri Sopian Hadi (Sekolah Tinggi Ilmu Tarbiyah (STIT) Syekh burhanuddin, 2023)
This research was motivated by students' lack of ability to understand mathematical concepts, students also had difficulty understanding what was conveyed by the teacher in class. Therefore, the aim of this research is to analyze students' understanding of mathematical concepts based on a guided discovery learning model (Discovery Learning) on algebraic material. This research was carried out at SMPN 2 Praya Timur. The subjects of this research were class VII, while the samples used were class VII B as the control class and class VII A as the experimental class. The instruments used in this research are the Learning Implementation Plan (RPP) with the Discovery Learning learning model and a written test in the form of essay questions with material in algebraic form. This research is a quantitative type of experimental research, the form is The Non Equivalent Control Group Design. Data analysis using the t test using the separated variance formula shows the results of the t test i.e then rejected. In this way, the results of this research are that the guided discovery learning model (Discovery Learning) is effective on students' ability to understand mathematical concepts at SMPN 2 Praya Timur.